Wrestling with technology: audiences, politics and the ecosystems of attendance during COVID-19. Issue 2 (4th May 2022) - Westerside, Andrew
ABSTRACT: Using a mixed methodology of case study analysis, qualitative methods and semi-longitudinal data analysis, this research asks how professional wrestling's 'techNo-fix' (Huesemann, Michael, and Joyce Huesemann. 2011. TechNo-Fix: Why Technology Won't Save Us or the Environment . Gabriola Island, Bc: New Society Publishers.) response to COVID-19 sought to remedy real or perceived voids in cultural and sporting participation since the global emergence of SARS-CoV-2 in March 2020. It considers the extent to which emerging, technologically driven models of event attendance are indeed 'fixes' at all, and identifies what such 'fixes' have therefore presupposed was 'broken', primarily in the social and/or aesthetic contract between performer and audience. The research examines spectator-performer and spectator-spectator relationships in live-broadcast events where in-arena audiences function as a form of paratext to the event-proper. In conclusion, the article considers to what extent these 'techno-fixes' are, in-and-of-themselves, responsible for creating emergent political, economic and ecological issues that require careful critical attendance for arts, culture and entertainment in a post-Covid landscape.